Spectral analysis using Haar wavelet (original signal, denoised signal, residual signal) and source level (SL) for whistle sound of dolphin (Tursiops aduncus) in captivity - Muhammad Z. Lubis; Pratiwi Dwi Wulandari; Sri Pujiyati; Totok Hestirianoto; Keni Sultan; Dwi P. I. Mahdi; Muhammad Mujahid (Aceh Journal of Animal Science, 2016)
This study discussed about Haar wavelet with a view original signal, denoised signal, and residual signal with using fourth whistle sounds of dolphin (Tursiops aduncus). The study was conducted in Safari Park, Cisarua, Bogor Indonesia with 2 dolphins. The results showed differences in results Haar wavelet, this study proves that the Haar wavelet is suitable for the analysis of dolphin sounds, and its have frequency ranged 8-22 kHz. The highest value of the noised signal was smaller than residual signal. The highest of residual signal contained in the second whistle, while the lowest was whistle 1, it showed that the larger the signal denoised result residual signal generated using Haar wavelet. The frequency of source level value ranged 8500 Hz to 11800 Hz, with the highest SL value was 43.9 dB (brown cyrcle). The lowest of the frequency of Source Level (SL) value ranged between 15700 Hz to 17990 Hz, with the lowest SL value was 38.5 dB (brown cyrcle). Whistle 1, 2, 3, and 4 have a different value SL and every SL values obtained in 1,2,3, and 4 have differences noise, it shows the same target but SL value and the sound patterns remain distinct by looking at time duration of whistle sound. Beam pattern from an omni directional sound source (DI= 0 dB, cyan trace) and a directional source following the piston model (DI= 18 dB, black  trace) and beam pattern with 4 types signal have ranged value 70 º-180°, with highest intensity value was 60º.